Perbandingan Motivasi Kerja Ruang Rawat Inap Dan Ruang Operasi Dalam Pelaksanaan Pendokumentasian Di RS MTSJ - Risma Tio Siahaan; Harsudianto Silaen (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
As providers of health services, hospitals are required to provide quality health services. Quality service is reflected in documentation in the form of client nursing notes. Nursing documentation is a very important tool that can be used as an indicator of the implementation of nursing care in hospitals (Fitri, 2019). Nursing care documentation is documentation that contains complete, real and recorded data, not only about the client's level of pain, but also the type, quality and quantity.